2013
DOI: 10.3168/jds.2012-5790
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Smartamine M or MetaSmart during the transition period benefits postpartal cow performance and blood neutrophil function

Abstract: The onset of lactation in dairy cows is characterized by severe negative energy and protein balance. Methionine availability during this time for milk production, hepatic lipid metabolism, and immune function may be limiting. Supplementing Met to peripartal diets with adequate Lys in metabolizable protein (MP) to fine-tune the Lys:Met ratio may be beneficial. Fifty-six multiparous Holstein cows were fed the same basal diet from 50 d before expected calving to 30 d in milk. From -50 to -21 d before expected cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
253
7
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(306 citation statements)
references
References 37 publications
(65 reference statements)
40
253
7
3
Order By: Relevance
“…In many feeding situations, supplementation of Met has been shown to increase milk protein content (Chen et al, 2011) and/or yield (Čermáková et al, 2012;Osorio et al, 2013) as well as milk fat content (Wang et al, 2010). This has also been confirmed in a recent systemic review of the literature (Robinson, 2010) and meta-analysis (Patton, 2010), and it agrees with our results in which milk protein and fat proportions increased modestly with the MET treatment.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In many feeding situations, supplementation of Met has been shown to increase milk protein content (Chen et al, 2011) and/or yield (Čermáková et al, 2012;Osorio et al, 2013) as well as milk fat content (Wang et al, 2010). This has also been confirmed in a recent systemic review of the literature (Robinson, 2010) and meta-analysis (Patton, 2010), and it agrees with our results in which milk protein and fat proportions increased modestly with the MET treatment.…”
Section: Discussionsupporting
confidence: 82%
“…This has also been confirmed in a recent systemic review of the literature (Robinson, 2010) and meta-analysis (Patton, 2010), and it agrees with our results in which milk protein and fat proportions increased modestly with the MET treatment. Patton (2010) suggests that a slight increase in milk yield can also be expected, and, even though this is consistent with the increases in milk yield reported earlier (Wang et al, 2010;Čermáková et al, 2012;Osorio et al, 2013), it does not agree with the reduction in milk lactose yield, or the tendency for milk yield to decrease with MET, in our study. A study by Robinson et al (2000), to determine effects of a Met oversupply, showed that abomasal Met infusion to increase its intestinal delivery by 34 to 39% markedly reduced animal performance.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The transition period for a high-producing dairy cow is metabolically stressful and it is during this time that most production diseases occur (Drackley, 1999;Ji et al, 2012;Osorio et al, 2013), most likely as a result of transient but sustained immunosuppression (Springer and Sciences, 2008). Many metabolomic and genomic studies have been performed to determine the role of macronutrients on gene expression of key metabolic pathways (Loor, 2010; Science Publications Mulligan and Doherty, 2008;Mulligan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%